The Influence of Interpersonal Communication and the Work Environment on Employee Performance at the Bulukumba Regency Fisheries Service Office - Yassir Arafah Hidayat; Samsul Rizal; Andi Risfan Rizaldi (Journal Social Society, 2026)
Employee performance remains a critical issue in public sector organizations, particularly in agencies responsible for delivering technical and community-based services. In the Fisheries Service Office of Bulukumba Regency, the need to strengthen coordination, task clarity, and service responsiveness provides the organizational context for examining factors that influence employee performance. This study aims to analyze the influence of interpersonal communication and work environment on employee performance. A quantitative explanatory design was applied using a census sampling technique involving all 60 employees as respondents. Data were collected through structured questionnaires measured with a five-point Likert scale and analyzed using descriptive statistics and multiple linear regression. The results show that interpersonal communication has a positive and significant effect on employee performance (? = 0.307; p = 0.001). The work environment also has a positive and significant effect on employee performance (? = 0.146; p = 0.003). Simultaneously, interpersonal communication and work environment significantly affect employee performance (F = 16.465; p = 0.001), with an R² value of 0.221, indicating that 22.1% of employee performance variation is explained by the model. These findings imply that management should improve employee performance by strengthening regular coordination meetings, establishing clearer feedback mechanisms, improving workplace facilities, and creating a more supportive organizational climate. Therefore, interpersonal communication and work environment are important determinants of employee performance in the Fisheries Service Office of Bulukumba Regency.